Perbedaan Regulasi Emosi pada Remaja Ditinjau dari Faktor Usia di Sekolah Yayasan Pendidikan Islam Swasta Amir Hamzah Medan - Alhila Rubiani; Shirley Melita Sembiring (Jurnal Diversita, 2018)
This research was conducted to observe the different emotion regulation in adolecences viewed from ages factor at YPI Swasta Amir Hamzah Medan school. Subject of research is primary school students, junior high school students and senior high school students at YPI Swasta Amir Hamzah Medan school which amounted 204 student. In this research technique for collecting samples used methods of proportional stratified random sampling. Methods of data collection using the scale of emotional regulation and identity sheet of respondents. Data analysis was performed with One Way Anova with F=23.212 and 0.000 < 0.05 as a significant coefficient. Based on the results of data analysis, the results obtained that there are differences in emotional regulation in adolescences in terms of ages factor in YPI Swasta Amir Hamzah Medan school. The late adolescence is known to have a good emotional regulation ability because the hypothetical mean (95) < the empirical mean (115.45) far exceeded the SD value (13.362) more than the middle adolescence and early adolescence. The ability of emotional regulation in the middle adolescence have a normal category because the hypothetical mean (95) < the empirical mean (105.29) exceeded the SD value (8.641) than the early adolescence is to have an emotional regulation in the medium category, because the hypothetical mean (95) > the empirical mean (103.59) more than the SD value (9.712).